Disturbance-Mediated Changes in Coral Reef Habitat Provoke a Positive Feeding Response in a Major Coral Reef Detritivore, Ctenochaetus striatus - Lin, Xianzhi; Hu, Simin; Liu, Yong; Zhang, Li; Huang, Hui; Liu, Sheng (Frontiers in Marine Science, 2021)
Coral reefs are undergoing global phase shifts from coral-dominated to algae-dominated stages. The negative effects of this substratum shift on the diversity and abundance of fish have been well documented, but the influence on fish feeding is less studied, which may limit a deeper understanding of trophic pathways in such a disturbed system. In this study, we investigated the feeding response of a numerically dominant fish species Ctenochaetus striatus to different substrate types, including hard coral, short algal turfs (SATs, <5 mm), and long algal turfs (LATs, >5 mm), on reefs in the South China Sea. The biomass of C. striatus showed an inverted U-shaped relationship with coral coverage and a significant positive correlation with SAT coverage (p < 0.05), indicating that rising SAT coverage associated with moderate coral loss provoked a feeding response in C. striatus. Stomach contents of C. striatus, analyzed using high-throughput sequencing (HTS), were dominated by algal sequences (relative read abundance, RRA > 80.0%), including macroalgae, filamentous algae, and microalgae (e.g., Symbiodinium and Prorocentrum). The sequence number and diversity of microalgae (mainly dinoflagellates) tended to be abundant (RRA 13.5–36.5%) with increased SAT cover, but brown algae sequences (RRA 17.2–57.8%) or green algae sequences (RRA > 50.7% except one site) dominated the stomach content DNA in reefs with high coral cover and high LAT or macroalgal cover, respectively. Considering the limited ability of C. striatus to remove mature algae, macroalgal DNA might be from algal debris. Our results indicate that C. striatus populations respond positively to conditions of moderate coral loss through increases in body condition identified as increased biomass. These responses are correlated to the expansion of SAT’s as coral cover declined, however, this relationship reverses if coral loss is high due to the succession of LAT’s over SAT’s and a corresponding decrease in the quality of food available. Our use of HTS has nevertheless identified the importance of detritivory in the flow of energy through reefs in the Anthropocene which are increasingly becoming depauperate in hard coral.